2018
DOI: 10.1530/joe-18-0362
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as target of endocrine-disrupting chemicals: implications for type 2 diabetes

Abstract: Type 2 diabetes is a chronic, heterogeneous syndrome characterized by insulin resistance and pancreatic β-cell dysfunction or death. Among several environmental factors contributing to type 2 diabetes development, endocrine-disrupting chemicals (EDCs) have been receiving special attention. These chemicals include a wide variety of pollutants, from components of plastic to pesticides, with the ability to modulate endocrine system function. EDCs can affect multiple cellular processes, including some related to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 233 publications
1
33
0
Order By: Relevance
“…Androgen precursors may contribute to the synthesis of estrogens, mediated by aromatase (CYP19) 62 . Estrogens are involved in mitochondrial metabolism and function 63 Mitochondria is a prevalent target of EDCs 64 Alteration of energy metabolism by mitochondrial dysfunctions has been associated to the exposure to several EDCs 65,66 . About 800 EDCs are considered as disrupters of mitochondrial membrane potential 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Androgen precursors may contribute to the synthesis of estrogens, mediated by aromatase (CYP19) 62 . Estrogens are involved in mitochondrial metabolism and function 63 Mitochondria is a prevalent target of EDCs 64 Alteration of energy metabolism by mitochondrial dysfunctions has been associated to the exposure to several EDCs 65,66 . About 800 EDCs are considered as disrupters of mitochondrial membrane potential 67 .…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial genome encodes proteins that are part of the ETC and are essential for ATP production, and it is well established that mutations in the mitochondrial genome predispose subjects to diabetes [12,14,15]. For instance, a recent prospective study carried out in individuals with mitochondrial disease found a higher incidence of endocrine disorders such as diabetes mellitus [13].…”
Section: Oxidative Stress In T2dmentioning
confidence: 99%
“…In light of this, EDCs may play a potential role in mitochondrial dysfunction, and their link with NAFLD has been proposed. Studies show that EDCs’ effects on mitochondrial bioenergetics, dynamics, biogenesis, and antioxidant capacity are implicated in the development of IR, T2DM, and MetS [ 104 , 105 ]. With this broad view, it has been shown that atrazine [ 106 ] and BPA [ 107 ] exert direct mitochondrial toxicity in HepG2 cells through the reduction in mainspring genes involved in mitochondrial function such as mitochondrial transcription factor A ( TFAM ) and sirtuin 1 ( SIRT1 ) and MRC interruption, which leads to a decrease in oxidative phosphorylation (OXPHOS) and ATP production.…”
Section: Mechanisms Of Action Of Endocrine-disrupting Chemicals In Nafldmentioning
confidence: 99%